Upaya Budidaya Ikan Skala Rumah Tangga (Budikruta) Untuk Menurunkan Angka Stunting di Desa Bangsalsari - Rendra C.Prasetya; Nadie Fatimatuzzahro; Dwi K.Apriyono; Miftahul Choiron; Amandia D.P.Shita (Fakultas Kedokteran Gigi, Universitas Jember, 2023)
Reducing Stunting Rate is a priority health program nationally. The stunting rate in Bangsalsari District is the 5 highest in Jember Regency. The COVID-19 pandemic is one of the factors that increased the stunting rate, as a result of economic problems in the community. Low family welfare and limited knowledge are the causes of difficulty in fulfilling family nutrition in a balanced manner. Lack of protein and calcium has an impact on the health of pregnant women and toddlers, malnourished toddlers, BBLR, is one of the factors causing stunting. The potential of natural resources, the background of the community as farmers and agroclimate conditions in Bangsalsari Village are potentials that can be utilized for the fulfillment of family nutrition independently, namely by household-scale fish farming (budikruta). Budikruta aimed to increase household income and increase protein and calcium intake for families. The targets of this program are housewives, posyandu cadres and stunting toddlers. This program will improve the nutritional status of stunting toddlers through the main Budikruta program, with companion programs independent toddler health monitoring training, Safe, Healthy, Simple, Whole, and Halal food processing training, supplementary feeding and increasing maternal awareness to maintain family health. There is an increase in the weight and height of stunted toddlers after this activity. The participation of all elements of society is needed to ensure the sustainability of the program.Keywords: Fish cultivation, Nutrition, Toddler, Stunting